Policy Network Implementation in Refugee Sheltering Places in Bintan - Sulastri, Tia; Samin, Rumzi; Adhayanto, Oksep (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
Abstract: Study This aim For research about networking policy in handling refugees in Indonesia who have arranged in regulation president number 125 of 2016 concerning handling refugees abroad. Handling includes; discovery, shelter, security and supervision immigration. For That study This focused just handling in place shelter precisely in the Regency Bintan. Goal: study This aim For know and describe role actor in handling refugees in place shelter Already walk Good or No as well as analyze factors What that's the only thing that hinders it in handling that. Method: the method used in study This is qualitative description, and technique data collection was found from observation, interviews and documentation. Results: livelihood show that each actor knows very well duties and functions in handling in place shelter refugees in Bintan. Interaction between actors too Good in do coordination after exists formation unit task in letter decision regent Bintan in 2019. But there is a number of findings problem yet resolved in accordance with applicable legislation. Conclusion: based on in study this., handling actors in Bhadra's Community House already Good with formation unit task in a convenient area actor coordinate. But actors too feel lack clear explanation in regulation president number 125 of 2016 concerning handling refugees overseas who haven't answer problem in the field.